MODERNIZED VEST DESIGN (KUTNU FABRIC - KARAOĞLAN, Hülya (Atlas Journal, 2021)
For designers in all industries, the topic of inspiration is a crucial issue for the efficiency of research. Cultural and traditional resources belonging to every region of Anatolia have inspired many designers around the world. Today, clothing is not produced solely to protect the body as it was in primitive ages. Clothing designs are also used in multifaceted concepts such as conveying emotional thoughts, problem solving, consistency, creativity, introducing cultures, and systematicity in the twenty-first century. Kutnu fabric, which has been produced on hand looms in Gaziantep region since the 16th century, was the inspiration for this work. Purpose of the study; Our aim is to help the promotion of kutnu fabric, which is one of our traditional values, to contribute to the increase in production demands, and to raise the awareness that this Anatolian fabric can be used in new generation young people. In this study, prehistoric development of weaving, which is one of the first occupations of Anatolian people, was briefly mentioned. The history of Kutnu fabric and vest clothing is explained, and the technical drawing, patterns and production stages of the vest produced using Kutnu fabric are presented with the support of pictures.